As práticas voltadas para a melhoria da governança no âmbito da Marinha do Brasil - Souza, Talita Rodrigues de (2017)
The aim of this study is to analyze how the adoption of practices and tools in the search for the improvement of governance in the Brazilian Navy in the context of the different types of military organizations that implement them. A bibliographic and documentary research was carried out on Quality Management, Quality in Brazilian Public Management, Excellence in Management and its fundamentals and criteria, and Quality Management in the Brazilian Navy. For the study, a qualitative methodology was used, through a multiple case study, which analyzed 30 organizations of the Brazilian Navy. As evidence that emerged from the study, it was pointed out that the nature of military organizations - operational, health, support and teaching - can be a determining factor in the adoption of practices aimed at improving governance. The main limitation of the research is the non-incorporation of the view of the actors involved in the studied reality through interviews, given the limited time to perform the research. Obtaining the perspective of managers and employees on the governance practices adopted would add information for a more complete analysis. Understanding the efforts to improve governance in the different military organizations of the Brazilian Navy can generate important clues for the continuous development of a quality program in the institution. With the need for public institutions to seek ways to become more efficient in the application of their resources, the study can contribute to the achievement of managerial objectives in order to meet the growing demands of Brazilian society. The present study contributes to broaden the scope of the evaluation of the efforts to improve governance in the military organizations of the Brazilian Navy.